And (a+b)(a−b) means (a+b) multiplied by (a−b). We use that a lot here!

## Special Binomial Products

So when we multiply binomials we get ... Binomial Products!

And we will look at three special cases of multiplying binomials ... So they are Special Binomial Products.

Bạn đang xem: The factors of a2

## 1. Multiplying a Binomial by Itself

What happens when we square a binomial (in other words, multiply it by itself) .. ?

(a+b)2 = (a+b)(a+b) = ... ?

The result:

(a+b)2 = a2 + 2ab + b2

This illustration shows why it works:

## 2. Subtract Times Subtract

And what happens when we square a binomial with a minus inside?

(a−b)2 = (a−b)(a−b) = ... ?

The result:

(a−b)2 = a2 − 2ab + b2

If you want lớn see why, then look at how the (a−b)2 square is equal to the big a2 square minus the other rectangles:

(a−b)2 = a2 − 2b(a−b) − b2 = a2 − 2ab + 2b2 − b2 = a2 − 2ab + b2

## 3. địa chỉ Times Subtract

And then there is one more special case ... What about (a+b) times (a−b) ?

(a+b)(a−b) = ... ?

The result:

(a+b)(a−b) = a2 − b2

That was interesting! It ended up very simple.

And it is called the "difference of two squares" (the two squares are a2 & b2).

This illustration shows why it works:

 a2 − b2 is equal lớn (a+b)(a−b)

Note: (a−b) could be first và (a+b) second:

(a−b)(a+b) = a2 − b2

## The Three Cases

Here are the three results we just got:

 (a+b)2 = a2 + 2ab + b2 } the "perfect square trinomials" (a−b)2 = a2 − 2ab + b2 (a+b)(a−b) = a2 − b2 the "difference of squares"

Remember those patterns, they will save you time và help you solve many algebra puzzles.

Xem thêm: Chứng Chỉ Toeic 450 Tương Đương Bậc Mấy? Ielts, Toeic Bao Nhiêu?

## Using Them

So far we have just used "a" and "b", but they could be anything.

### Example: (y+1)2

We can use the (a+b)2 case where "a" is y, và "b" is 1:

(y+1)2 = (y)2 + 2(y)(1) + (1)2 = y2 + 2y + 1

### Example: (3x−4)2

We can use the (a-b)2 case where "a" is 3x, and "b" is 4:

(3x−4)2 = (3x)2 − 2(3x)(4) + (4)2 = 9x2 − 24x + 16

### Example: (4y+2)(4y−2)

We know the result is the difference of two squares, because:

(a+b)(a−b) = a2 − b2

so:

(4y+2)(4y−2) = (4y)2 − (2)2 = 16y2 − 4

Sometimes we can see the pattern of the answer:

### Example: which binomials multiply lớn get 4x2 − 9

Hmmm... Is that the difference of two squares?

Yes!

4x2 is (2x)2, and 9 is (3)2, so we have:

4x2 − 9 = (2x)2 − (3)2

And that can be produced by the difference of squares formula:

(a+b)(a−b) = a2 − b2

Like this ("a" is 2x, and "b" is 3):

(2x+3)(2x−3) = (2x)2 − (3)2 = 4x2 − 9

So the answer is that we can multiply (2x+3) and (2x−3) to get 4x2 − 9